2015
DOI: 10.1016/j.jtcvs.2015.07.027
|View full text |Cite
|
Sign up to set email alerts
|

The no-touch saphenous vein for coronary artery bypass grafting maintains a patency, after 16 years, comparable to the left internal thoracic artery: A randomized trial

Abstract: Harvesting the SV with the NT technique conferred, at a mean time of 16 years, a significantly higher patency than the conventional technique that was still comparable to that of the LITA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
200
3
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(212 citation statements)
references
References 33 publications
4
200
3
5
Order By: Relevance
“…They concluded that harvesting SVG with surrounding tissue provided excellent short-and long-term patency, which was comparable to the IMA [75].…”
Section: Cabg Using Saphenous Vein Graftsmentioning
confidence: 87%
“…They concluded that harvesting SVG with surrounding tissue provided excellent short-and long-term patency, which was comparable to the IMA [75].…”
Section: Cabg Using Saphenous Vein Graftsmentioning
confidence: 87%
“…A final drawback of the study could have resulted from the conventional technique of harvesting the vein grafts in this study opposed to the no-touch technique that has been recommended by some groups, because it provided a significantly higher patency [24] and left ventricular ejection fraction [25] at a mean time of 16 years than the conventional technique.…”
Section: Study Limitationsmentioning
confidence: 97%
“…9) Permeability rates using this procedure are of 83% at 16 years compared to an 88% in arterial grafts. 9) Regarding the morphology of the SV, a Turkish study reported a mean length of 72.42 ± 6.60 cm. 20) The luminal diameter varies in proximal, medial, and distal segment itself, thus avoiding distension prior to anastomosis, 31,32) which can cause intimal and medial hyperplasia, leading to graft failure.…”
Section: Coronary Arteriesmentioning
confidence: 99%
“…In order to achieve this, it is necessary to complete the revascularization using ducts that will remain permeable for all or most of the patient's life. 4,9) There is a wide variety of vascular conduits available for CABG. The most commonly used are as follows: internal thoracic artery (ITA), saphenous vein (SV), radial artery (RA), right gastroepiploic artery (RGEA), and occasionally ulnar artery (UA), splenic artery, and inferior epigastric artery.…”
mentioning
confidence: 99%